Hydrolysis of triple-helical collagen peptide models by matrix metalloproteinases. - Lauer-Fields, J; Tuzinski, K; Shimokawa, K; Nagase, H; Fields, G (2000)
The matrix metalloproteinase (MMP) family has been implicated in the process of a variety of diseases such as arthritis, atherosclerosis, and tumor cell metastasis. To study the mechanisms of MMP action on collagenous substrates, we have constructed homotrimeric triple-helical peptide (THP) models of the collagenase cleavage sites in types I and II collagen. The THPs incorporate either the alpha1(I)772-786 or the alpha1(II)772-783 sequence. The alpha1(I)772-786 and alpha1(II)772-783 THPs were hydrolyzed by MMP-1 at the Gly-Ile and Gly-Leu bonds, respectively, analogous to the bonds cleaved in corresponding native collagens. Thus, the THPs contained all necessary information to direct MMP-1 binding and proteolysis. Subsequent investigations using the alpha1(I)772-786 THP showed hydrolysis by MMP-2, MMP-13, and a COOH-terminal domain-deleted MMP-1 (MMP-1(Delta(243-450))) but not by MMP-3 or a COOH-terminal domain-deleted MMP-3 (MMP-3(Delta(248-460))). Kinetic analyses showed a k(cat)/K(m) value of 1,808 s(-1) m(-1) for MMP-1 hydrolysis of alpha1(I)772-786 THP, approximately 10-fold lower than for type I collagen. The effect is caused primarily by relative K(m) values. MMP-2 and MMP-13 cleaved the THP more rapidly than MMP-1, but MMP-2 cleavage occurred at distinct multiple sites. Comparison of MMP-1 and MMP-1(Delta(243-450)) hydrolysis of alpha1(I)772-786 THP showed that both can cleave a triple-helical substrate with a slightly higher K(m) value for MMP-1(Delta(243-450)). We propose that the COOH-terminal domain of MMPs is necessary for orienting whole, native collagen molecules but may not be necessary for binding to and cleaving a THP. This proposal is consistent with the large distance between the MMP-1 catalytic and COOH-terminal domains observed by three-dimensional structural analysis and supports previous suggestions that the features of the catalytic domain contribute significantly toward enzyme specificity.